Pros and Cons of Aspirin for the Primary Prevention of Cardiovascular Events: A Secondary Study of Trial Sequential Analysis - Zhao, Binghao; Wu, Qian; Wang, Li; Liao, Chen; Dong, Yifei; Xu, Jingsong; Wei, Yiping; Zhang, Wenxiong (Frontiers in Pharmacology, 2021)
Background and aims Aspirin leads to substantial benefits for the secondary prevention of cardiovascular disease (CVD). We aimed to cast more light on aspirin’s role for the primary prevention of CVD. Methods Databases were searched for clinical trials comparing aspirin vs. no aspirin use in this meta-analysis. Efficacy and safety profiles were rigorously investigated. Trial sequential analysis (TSA) was used to determine the robustness of the results. Results Fourteen studies with 163 840 participants were eligible (mean follow-up 6.2 y). Aspirin intake was found to be associated with 9%, 13%, and 12% reductions in the risk of cardiovascular events (CV events) (relative risk [RR]: 0.91, 95% confidence intervals [CI]: 0.87-0.96; risk difference (RD): 0.29%; absolute risk percentage (AR%): 7.61%; number needed to treat (NNT): 345), myocardial infarction (RR: 0.87, 95% CI: 0.77-0.97; RD: 0.21%; AR%: 11.11%; NNT: 488) and ischaemic stroke (RR: 0.88, 95% CI: 0.80-0.96; RD: 0.21%; AR%: 16.14%; NNT: 476), respectively; aspirin intake was also associated with 40%, 30%, and 57% increases in the risk of major bleeding (RR: 1.40, 95% CI: 1.29-1.53; RD: 0.47%; AR%: 27.85; NNT: 214), intracranial bleeding (RR: 1.30, 95% CI: 1.11-1.52; RD: 0.10%; AR%: 22.99%; NNT: 1000) and major gastrointestinal bleeding (RR: 1.57, 95% CI: 1.38-1.78; RD: 0.32%; AR%: 36.70%; NNT: 315), respectively. Further, populations with low doses of aspirin intake (≤ 100 mg), populations < 65 y old or populations with body mass index (BMI) ≧ 25 experienced more advantages; high-risk (10-y cardiovascular risk ≧10%) and full diabetic individuals reported hardly clinical benefits. Conclusions Aspirin intake was associated with a reduced risk of CV events and an increased incidence of bleeding profiles in primary prevention. It is necessary to identify individual’s CVD risk using clear examinations or assessments before aspirin intake, and truly realize individualized prescription.